Analysis of differences in anatomical information in magnetic resonance cholangiopancreatography (MRCP) examinations between the use of the mouth breath hold technique and trigger technique - Rahmawan, Sahrul; Fitriana, Lutfatul; Hidayat, Fathur Rachman; Samudra, Alan (Institute of Computer Science (IOCS), 2025)
MRCP is a non-invasive imaging method used to visualize the biliary system and detect abnormalities in the bile ducts or gall bladder. In taking images, there are two techniques, namely the mouth breath hold (MBH) technique and the trigger technique, where the MBH technique is carried out by the radiographer giving instructions directly related to the patient's respiratory movements, while the trigger technique uses respiratory gating to detect breathing patterns and minimize image blur due to organ movement. At Department of Radiology SMC Telogorejo Semarang both techniques are used in MRCP examinations by looking at the condition of each patient. So the author is interested in comparing the results of anatomical information from the two techniques. Methods: This research uses a quantitative design with an experimental approach. Data was collected from 10 patients who underwent MRCP examinations at the Department of Radiology SMC Telogorejo Semarang in August–September 2024. The scanning procedure was carried out using a T2 HASTE coronal section sequence twice for each patient using the MBH and trigger technique. Anatomical information was assessed by means of visual grading analysis by 3 radiologists on the structure of the cystic duct, intra-hepatic duct, common hepatic duct, common bile duct, pancreatic duct, and gallbladder (gallbladder) using a questionnaire with a scale (1–4). Then the data was analyzed using SPSS to determine whether there were differences in image information from the two techniques using the Wilcoxon difference test. This research has passed the ethical test number: KEPK/UMP/170/I2025. Results: Based on the results of the Wilcoxon test, both for the entire anatomy and for each anatomy, it shows a p-value < 0.05. This indicates that there are significant differences in the anatomical information produced by the two techniques. Based on the mean rank value, the most optimal technique for displaying anatomical information is MBH. This advantage is due to its ability to reduce movement artifacts through the breath-hold method, resulting in clearer and more detailed anatomical images compared to the trigger technique. The MBH technique is more effective in improving MRCP anatomical information, especially in patients with respiratory instability. It is hoped that these results can be a reference in determining the optimal method for MRCP examination.